Phylogenetic evidence for underreporting of male‐to‐male sex among human immunodeficiency virus–infected donors in the Netherlands and Flanders. Issue 5 (4th April 2017) - van de Laar, Thijs J.; Bezemer, Daniela; van Laethem, Kristel; Vandewalle, Giovani; de Smet, Annie; van Wijngaerden, Eric; Claas, Eric C.; van Sighem, Ard I.; Vandamme, Anne‐Mieke; Compernolle, Veerle; Zaaijer, Hans L.
Abstract : BACKGROUND: Separate transmission networks for human immunodeficiency virus (HIV) coexist. Molecular typing of viral genomes can provide insight in HIV transmission routes in donors for whom risk behavior–based donor selection failed. STUDY DESIGN AND METHODS: This study includes all HIV‐infected Dutch and Flemish donors in the period 2005 to 2014 (n = 55). Part of the HIV polymerase (pol) gene was amplified, sequenced, and compared with more than 10, 000 HIV strains obtained from HIV‐infected Dutch and Flemish patients. The most likely transmission route was determined based on HIV phylogeny and the donor's self‐reported risk behavior during the exit interview. RESULTS: HIV‐infected donors were predominantly male (69%), were repeat donors (73%), were born in the Netherlands or Belgium (95%), and harbored HIV Subtype B (68%). Seventy‐five percent of HIV‐infected male donors were part of robust phylogenetic clusters linked to male‐to‐male sex, while only 24% of HIV‐infected male donors reported male‐to‐male sex during posttest counseling. Sex between men and women accounted for 13% of HIV infections in male donors and 93% of HIV infections in female donors based on phylogenetic analysis. Only 40% of HIV‐infected female donors had HIV Subtype B; 65% of female donors reported a foreign partner and indeed HIV sequences interspersed with sequences from HIV‐endemic areas abroad, in particular sub‐Saharan Africa. CONCLUSION: HIV typing helps to understand HIV transmission routes in donor populations. We found substantial underreporting of male‐to‐male sex among HIV‐infected male donors. Donor education on HIV risk factors and the danger of window‐period donations and a donor environment that encourages frank disclosure of sexual behavior will contribute to a decrease of HIV‐infected donors.